The Role and Importance of Training and Tactical Training in Higher Education in Reducing Fire Risk - S. T., Ruziev; A. M., Achilov; M. Sh, Kamalova (European Journal of Life Safety and Stability (2660-9630), 2022)
The article aims to reduce the amount of material losses from fires in the population and regions by analyzing the statistics of fires in the country to ensure fire safety of sectors of the economy, critical and classified facilities.